Karate Sports and its History - Imamnazarovich, Bazarov Komiljon (European Journal of Life Safety and Stability (2660-9630), 2021)
We know that karate, which has a long history, has received a lot of attention in the past. This article talks about the history of karate, its development, and its inclusion in the Olympic program.